The effect of Ba Duan Jin exercise intervention on cardiovascular disease: a meta-analysis of randomized controlled trials - Chen, Jiali; Zhang, Man; Wang, Yihao; Zhang, Ziyu; Gao, Shuyan; Zhang, Yafei (Frontiers in Public Health, 2024)
Background: Exercise therapy, as a means to prevent and treat cardiovascular diseases, has been gradually applied in clinical practice. It has the advantages of reducing mortality, improving clinical symptoms, restoring physical function and improving quality of life. Objective: To investigate the effect of Ba Duan Jin exercise intervention for the primary prevention of cardiovascular diseases. Methods: Eight databases were systematically searched from inception to July, 2024 for randomized controlled trials (RCTs) to evaluated the impact of Ba Duan Jin exercise intervention on cardiovascular diseases. The search terms were “Cardiovascular diseases” “Ba Duan Jin” and “Randomized controlled”. The Cochrane risk assessment tool was used to evaluate the study quality, and the meta-analysis was performed using Rev Man 5.4 software. Results: Seventeen completed trials were conducted with 1,755 participants who were randomly assigned and met the inclusion criteria. All 17 studies were conducted in China. The meta-analysis indicates that Ba Duan Jin exercise therapy can provide long-term benefits (20-30 years) by reducing all-cause mortality (RR=0.55, 95% CI: 0.44-0.68, P < 0.01)) and stroke mortality (RR=0.49, 95% CI: 0.36-0.66, P < 0.01) in hypertensive patients. Subgroup analyses reveal that Ba Duan Jin exercise therapy decreases SBP (MD = -4.05, 95% CI = -6.84 to -1.26, P < 0.01) and DBP (MD = -3.21, 95% CI= -5.22 to -1.20, P < 0.01) levels in patients with essential hypertension, significantly reduces serum TC (MD = -0.78, 95% CI = -1.06 to -0.50, P< 0.01), TG (MD = -0.78, 95% CI=- 0.93 to -0.62, P < 0.01), and LDL-C (MD = -0.76, 95% CI = -0.92 to -0.60, P < 0.01) levels in patients with hyperlipidemia, increases HDL-C (MD=0.32, 95% CI=0.14-0.51, P < 0.01) levels, and produces beneficial effects on cardiovascular function. Additionally, it can alleviate anxiety (MD=-3.37, 95% CI=-3.84 to -2.89, P <0.01) and improve sleep quality (MD=-2.68, 95% CI=-3.63to -1.73, P < 0.01). Conclusion: Ba Duan Jin exercise therapy can improve the physical and mental condition and quality of life of patients with cardiovascular diseases, and it is worthy of further promotion and application in clinical practice. Systematic Review Registration: PROSPERO, identifier: CRD42024496934.